Exploring the active ingredients and pharmacological mechanisms of the oral intake formula Huoxiang Suling Shuanghua Decoction on influenza virus type A based on network pharmacology and experimental exploration - Tang, Ruying; Wang, Linyuan; Zhang, Jianjun; Li, Xinyu; Tan, Lingyun; He, Wei; Han, Hui; Liu, Yuan; Wang, Keyu; Wang, Mengyao (Frontiers in Microbiology, 2022)
Objective: Investigating the active ingredients, underlying anti-influenza virus effects and mechanisms of Huoxiang Suling Shuanghua Decoction (HSSD). Methods: The therapeutic effect of HSSD were confirmed through the survival rate experiment of H1N1 infection mice. Then the HSSD solution and the ingredients absorbed into the blood after treating with HSSD in rat were identified respectively by UPLC/Q-TOF MS, while main contents of ingredients detecting by HPLC. Next, a systems pharmacology approach incorporating target prediction, GO enrichment, KEGG pathway analysis and molecular docking were performed to screen out the active compounds and critical pathways of HSSD in treating influenza. According to prediction results, RT-qPCR and immunohistochemistry assay were used to detect the mRNA and protein expression levels of critical targets in H1N1 infecting mice lung. Results: HSSD improved the survival rate of H1N1 Infected mice and prolonged the mice lifespan. Besides, HSSD exerts antivirus effect by decreasing the levels of HA and NP to inhibit the replication and proliferation of H1N1, reducing the lung pathological state, inhibiting the cell apoptosis in lung, and regulating the abnormal responses of peripheral blood including GRA, LYM, WBC, PLT, HGB. Then, 87 compounds in HSSD solution and 20 ingredients absorbed into blood after treating with HSSD were identified. Based on this, combining with the network analysis and previous researches of antivirus, 16 compounds were screened out as the active components. Moreover, 16 potential targets were predicted by network pharmacology analysis. Next, molecular docking results shown the stable binding modes between compounds and targets. Furthermore, experimental validation results indicated that HSSD regulating the contents of IgA, IgM, and IgG in serum, modulating the levels of IFN-γ, IL-6, IL-10, MCP-1, MIP-1α, and IP-10 in lung tissue, and significantly decreasing the mRNA and protein expressions of TLR4, CD14, MyD88, NF-κB p65, HIF1 α, VEGF, IL17A, and IL6 in lung tissue. Conclusion: HSSD exerts anti-influenza effect by affecting the mRNA and protein expressions of TLR4, CD14, MyD88, NF-κB p65, HIF1 α, VEGF, IL17A, and IL6, involving directly antiviral and the inhibition of the accumulation of inflammation. Our study provided experimental evidences about the practical application of HSSD in treating influenza.